CHANGES IN THE COMPOSITION OF THE CATALYST DEPENDING ON THE PRODUCTION METHOD, ENVIRONMENT AND TEMPERATURE WHEN CALVING DIFFERENT ENVIRONMENTS - Saliхova Ozoda Abdullayeva; Sidikova Gulchekhra Abdujalolovna (Galaxy International Interdisciplinary Research Journal, 2024)
In order to study the effect of the support on the activity of aluminum-nickel-molybdenum catalysts, samples were prepared using aluminum oxide (bulk weight 0.70 g/cm3). Samples were prepared by coprecipitation (sample BF-2a) and impregnation (sample BF-9a). The test results showed that samples prepared by impregnation of alumina have increased activity compared to catalysts prepared using standard alumina. In this case, samples calcined in a nitrogen environment have the greatest activity.